Comparative transcriptomics analysis of Zygosaccharomyces mellis under high-glucose stress - Gongliang Liu; Xinyu Bi; Changli Tao; Yongtao Fei; Sujuan Gao; Jinglong Liang; Weidong Bai (Food Science and Human Wellness)
The high-glucose tolerance of yeast is the main factor determining the efficiency of high-density alcohol fermentation. Zygosaccharomyces mellis LGL-1 isolated from honey could survive under 700 g/L high-glucose stress and its tolerant characteristics were identified in our previous study. This study was performed to explore and clarify the high-glucose tolerance mechanism of Z. mellis LGL-1. Comparative transcriptomic analysis was used to analyze the genes with differential expression in Z. mellis under high-glucose conditions of 300, 500 and 700 g/L. With 300 g/L samples as reference, there were 937 and 2380 differentially expressed genes (DEGs) in the 500 and 700 g/L samples, respectively. Meanwhile, there was 825 significant DEGs in the 700 g/L samples compared with that of the 500 g/L samples. The result revealed that transcriptional changes in multiple metabolic pathways occur in response to high-glucose stress. q-RT PCR analysis further confirmed that several stress response pathways, such as the high osmolarity glycerol mitogen-activated protein kinase (HOG-MAPK) signal transduction pathway, trehalose synthesis pathway and oxidative stress response are closely related to high-glucose tolerance in Z. mellis. This study clarifies mechanisms of Z. mellis in response to high-glucose osmotic stress, providing theoretical basis for the process control of high-density alcohol fermentation.